Immunization against GAD induces antibody binding to GAD-independent antigens and brainstem GABAergic neuronal loss. - Thashi Chang; Harry Alexopoulos; Philippa Pettingill; Mary McMenamin; Robert Deacon; Ferenc Erdelyi; Gabor Szabó; Camilla J Buckley; Angela Vincent (PLoS ONE)
Stiff person syndrome (SPS) is a highly-disabling neurological disorder of the CNS characterized by progressive muscular rigidity and spasms. In approximately 60-80% of patients there are autoantibodies to glutamic acid decarboxylase (GAD), the enzyme that synthesizes gamma-amino butyric acid (GABA), the predominant inhibitory neurotransmitter of the CNS. Although GAD is intracellular, it is thought that autoimmunity to GAD65 may play a role in the development of SPS. To test this hypothesis, we immunized mice, that expressed enhanced green fluorescent protein (EGFP) under the GAD65 promoter, with either GAD65 (n = 13) or phosphate buffered saline (PBS) (n = 13). Immunization with GAD65 resulted in autoantibodies that immunoprecipitated GAD, bound to CNS tissue in a highly characteristic pattern, and surprisingly bound not only to GAD intracellularly but also to the surface of cerebellar neurons in culture. Moreover, immunization resulted in immunoglobulin diffusion into the brainstem, and a partial loss of GAD-EGFP expressing cells in the brainstem. Although immunization with GAD65 did not produce any behavioral abnormality in the mice, the induction of neuronal-surface antibodies and the trend towards loss of GABAergic neurons in the brainstem, supports a role for humoral autoimmunity in the pathogenesis of SPS and suggests that the mechanisms may involve spread to antigens expressed on the surface of these neurons.